Correlation between duration of varicocele and apoptosis in testicular tissue in an experimental model - (:unkn) unknown (ELSEVIER SCIENCE INC, 2008)
OBJECTIVES To experimentally demonstrate the negative effect of a waiting period for treatment in patients with varicocele. METHODS A varicocele group of 30 rats and a sham group of 10 were used. All rats in the varicocele groups underwent ligation in the left testicle proximal to the site at which the internal spermatic vein drains into the renal vein to constrict the vein by 50%. In the sham group, the renal vein was dissected but not ligated. One month later, the first P) rats in the experimental group and the first 5 rats in the sham group underwent laparotomy and bilateral orchiectomy. At 2 months postoperatively, the same procedures were performed on the second group of rats (15 varicocele rats and 5 sham rats). The apoptotic index was evaluated by group and interval after varicocele or sham operation. For apoptosis detection, modification of in situ end labeling was used. RESULTS At 1 and 2 months after creation of the varicocele or sham operation, the apoptosis rate in the left varicocele group was significantly greater than in the sham group (P <0.001) or in the right testicles (P <0.001). Although an increase in the apoptosis rate was seen in the second month compared with the first month, the difference was not statistically significant (P = 0.875). The histopathologic finding of atrophy was more significant in the second month than in the first month in the varicocele group. CONCLUSIONS The results of our study have indicated that the increase in apoptosis at the end of the first month in the varicocele group was significant and that this apoptosis continued with time. Because the histopathologic injury, which is parallel to apoptosis, increased, we believe that treatment in the early phase of varicocele is important for prevention of probable injury.
Keywords: GERM-CELL APOPTOSIS; RAT TESTIS; MEN